Thermophysical Model of (269) Justitia—Main Belt Asteroid Possibly Implanted from Trans-Neptunian Region - Anna Marciniak; Antoine Choukroun; Julia Perła; Waldemar Ogłoza; Robert Szakáts; Pierre Antonini; Raoul Behrend; Géza Csörnyei; Marek Dróżdż; Marcel Fauvaud; Stéphane Fauvaud; Adrian Jones; et al. (The Planetary Science Journal)
Asteroid Justitia is a special main-belt object, being an extremely red body with a steeper spectral slope than any other D-type asteroid. Conversely, its spectral and polarimetric properties resemble organics-rich Centaurs and trans-Neptunian objects. For this reason, it was chosen as a main target of the MBR Explorer space mission. It is crucial for space mission planning and operations to have in advance the best estimate of the target size, spin, shape, and properties of the surface. In particular, the size determination was in high demand before the extensive stellar occultation campaign in 2023 August, for station deployment and observation planning. We utilized multiple lightcurves from our campaign on slow rotators and from the literature to reconstruct the spin and shape of Justitia via lightcurve inversion. Then we applied the Convex Inversion Thermophysical Model to simultaneously optimize the fit to visible lightcurves and to thermal data from infrared space observatories. We present here the pair of most precise physical models of Justitia possible before the occultation campaign, with similar properties of both solutions. The size range of Justitia was narrowed here to 55–60 km, so by a factor of 4 compared with previous estimates, and also the shape model's resolution was improved. An estimate of thermal inertia and surface roughness was also obtained, with implications for surface texture and regolith properties.